IMPLEMENTASI PERAN HAKIM PENGAWAS DAN PENGAMAT DI LEMBAGA PEMASYARAKATAN KELAS II B BANGKINANG - Khodikatul Janna; Evi Deliana; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Judges have independent power which means that they are free from the influence of any party. Apart from carrying out their main duties, namely examining, hearing and deciding cases in court, judges also have other important duties and roles. Another task is the task of supervising and observing the development of prisoners in the correctional institutions so that they run well and be successful. The Supervisory and Observing Judges are regulated in the Criminal Procedure Code Articles 277-283 and also the Supreme Court Circular Letter Number 7 of 1985 concerning Guidelines for the Implementation of the Duties of Supervisory and Observing Judges. However, in the current reality, the role of the Supervisory Judge and observer is not running properly as it should have been regulated by law. The problems that will be answered in this thesis are, the role of Supervisory Judges and Observers in Bangkinang Class II Correctional Institution, Obstacles faced by supervisory judges and observers to the pattern of guiding prisoners in Class II B Bangkinang Correctional Institutions, furthermore the importance of supervision and observation by judges who supervise and observe the pattern of guiding prisoners in Bangkinang Class II Correctional Institutions and how it affects the increase in the crime rate.This type of research can be classified as sociological, because in this study the author directly conducted research at the location or place under study in order to provide a complete and clear picture of the problem under study. This research was conducted at the Bangkinang Class II B Prison and the Bangkinang District Court, while the population and sample were all parties related to the problems studied in this study, the data sources used were primary data, secondary data, and tertiary data, data collection techniques. in this study with observation, interviews, questionnaires, and literature study.From the research results, it can be concluded that, first, the role of the Supervisory Judge and Observer has not been going well and successfully. Second, the obstacles faced by the Supervisory Judge and Observer are the large number of activities in the Court and the lack of facilities and infrastructure. Third, the importance of the role of the supervisory judge and observer greatly affects the increasing number of crimesKeywords: Role - Supervisory Judge and Observer - Prisoners